Evaluation of Road Geometry to Tourism Areas (Case Study: East Ring Road - Jatigede Dam, Sumedang - Indonesia) - Febri Kusbianto Pamungkas; Jody Martin Ginting (Fakultas Teknik Sipil dan Perencanaan, 2024)
Road geometry design is a method of planning roads geometrically or involving the computation of angles through a process. For road geometric design, it is necessary to assess the suitability of design criteria with applicable guidelines, namely the Road Geometric Design Guidelines. Therefore, this study will conduct a geometric design assessment of the application of the existing road geometric design of the Jatigede East Ring Roads and adjust it to the